Urgency of Fiscal Policy to Overcome Welfare Gap in Indonesia - Abdul Aziz (Journal of Economics and Behavioral Studies, 2019)
Abstract: This study aims to describe the condition of the welfare gap between residents and regions in Indonesia on a number of welfare indicators namely poverty depth index, poverty severity index, Gini Coefficient Index (GCI), and the Human Development Index (HDI). This study also aims to analyze the importance of fiscal policy, especially in the form of state expenditure allocations to minimize the gap. This study uses a quantitative descriptive analysis method that is by calculating some of the indicator data needed through the approach of average value, termun, standard devasi, and others. The result is a description of the welfare gap between people / regions in Indonesia and an overview of government policies that have been carried out. Whereas one of the recommendations is that the government should allocate state expenditures that are more effective, efficient, quality and pay attention to priority scale so that it can solve the welfare gap problem above.